Effectiveness of the school nurse role in increasing the vaccination coverage rate: a narrative review - Guarinoni, M. G.; Dignani, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Introduction. Vaccinations are recognized as the best primary prevention strategy to counteract infectious diseases. However, in recent years, there has been a decrease in the immunization rate, particularly among children and teenagers. Several strategies have been tested to circumvent the issue. Among them, there was the re-introduction of vaccination practices in schools.The literature shows that introducing immunization projects in schools has increased vaccination rates in children and teenagers, but the role of the school nurse in these settings has never been evaluated. AIM. To determine whether the role of the school nurse, within the school vaccination projects, does have a positive impact on the rate of immunization’s compliance.Methods. Narrative review. Studies of primary, secondary and gray literature were included, researched on Cochrane Central Register of Controlled Trials, MEDLINE, EMBASE, CINAHL, Science Citation Index and Web of Science. Nine articles based on studies conducted in different educational institutions (from kindergarten to high school) were included in the review.Results. All the articles included in the review showed that the interventions conducted by the school nurse, aimed at increasing the rate of adhesion to vaccinations, are effective. Discussion and Conclusions. The literature related to the topic of the present study shows that the school nurse plays a key role in increasing the rate of adhesion to immunization for school-age children / adolescents. The figure of the school nurse plays a crucial role in increasing the rate of adhesion to immunization’s programme for school-age children. However, in several countries, including Italy, this figure was present in the past but does not exist now. The lack of the school nurse’s role in these countries does not allow the activation of programs focused on this figure’s capacity.